Murid rodents (Muriformes, Muridae) from Trascarpathia in the collections of Kyiv zoological museums - Barkasi, Z. (Збірник праць Зоологічного музею, 2014)
In scientific collections of the National Museum of Natural History, NAS of Ukraine and the Zoological Museum of Kyiv Taras Shevchenko National University are preserved 482 samples, six species of Muridae rodents collected from 1940 to 1990. Specimens were collected in all altitudinal zones of the region. The article containes general characteristics of the collections and brief description of genera and species of murids according to the latest fauna surveys of the region.